2002
DOI: 10.5713/ajas.2002.1507
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality and Variation of Meat and Bone Meal

Abstract: Meat and bone meal is a valuable protein and mineral source in diets of production animals and contributes to the protein, energy and mineral component of diets. The aim of the present study was to more accurately characterise the apparent ileal amino acid digestibility of meat and bone meals produced in New Zealand and evaluate routine in vitro assays used in practise to measure meat and bone meal quality. A total of 94 commercial meat and bone meals from 25 New Zealand rendering plants over a two and a half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
54
6
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 26 publications
7
54
6
3
Order By: Relevance
“…The first risk is that the by-products, also after rendering procedures, would carry a residual TSE infectivity (Taylor et al, 1995). The second issue arises from the nutritive value of the treated material after the intense heat treatment, usually applied to the animal waste, especially for the production of protein hydrolyzates (Piva et al, 2001;Hendriks et al, 2002Hendriks et al, , 2006. Exposure to proteins to certain processing conditions induces two major chemical changes, racemization of amino acids and formation of cross-linked amino acid (Liardon and Hurrell, 1983;Man and Bada, 1987;Friedman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The first risk is that the by-products, also after rendering procedures, would carry a residual TSE infectivity (Taylor et al, 1995). The second issue arises from the nutritive value of the treated material after the intense heat treatment, usually applied to the animal waste, especially for the production of protein hydrolyzates (Piva et al, 2001;Hendriks et al, 2002Hendriks et al, , 2006. Exposure to proteins to certain processing conditions induces two major chemical changes, racemization of amino acids and formation of cross-linked amino acid (Liardon and Hurrell, 1983;Man and Bada, 1987;Friedman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Meat and bone meal (MBM) has been widely used as a valuable protein and mineral source in diets of production animals (Hendriks et al 2002). Development of animal transmissive spongiform encephalopathies (TSE), like ovine scrapie and bovine spongiform encephalopathy (BSE) has been linked to feeding ruminants with MBM contaminated with transmissive agents (Brewer 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Animal source ingredients, such as the meat and bone meal (MBM), contain high levels of available P (Jeng et al, 2006) as well as other minerals. Hendriks et al (2002) reported that the mean ash content of 94 MBM samples tested was 28.4%. In comparison, plant source ingredients contain a high percentage of phytate P, which cannot be utilized by poultry.…”
Section: Introductionmentioning
confidence: 99%